O direito real de habitação na sucessão do convivente supérstite - Dutra, Camila Moreira Barros (2007)
The present work boards the controversy over the straight law of habitation as a figure of right of succession in the case of the death of the one of the parties in a common-law marriage. It has been stablished a parallel among these rights conceded to the husbands or wives and those conceded to the parties of the common-law marriage at the present standing normative system. According to this, a critical analysis has been made with the familiar entities disposed by the Federal Constitution and its abordage by the infraconstitutional rules. Essencial to the proposed object, the study has been expanded to the elements of the family rights, the straight law and the rights of succession, having as an aim the examining of this law application over the surviving part in a common-law marriage